Функциональная оценка типов гистохимической структуры мышц крыла некоторых Phasianidae - Сыч, В.Ф. (Вестник зоологии, 1980)
Muscles of the shoulder girdle and free extremity in Phasianus colchicus and Coturnix japonica are of mixed structure and include R (red), W (white) and I (interme diate) fibres. Taking into account a quantitative ratio of these fibres in musclecompo sition 6 histochemical muscle types are distinguished corresponding to different models of muscles contraction as organs. The results of analysis of histochemical structure of muscles permit their functional potentialities to be specified and characteristic features of flying qualities and types of flight in the bird species under study to be explained.